A Homozygous PDE6D Mutation in Joubert Syndrome Impairs Targeting of Farnesylated INPP5E Protein to the Primary Cilium. Issue 1 (13th November 2013) - Thomas, Sophie; Wright, Kevin J.; Corre, Stéphanie Le; Micalizzi, Alessia; Romani, Marta; Abhyankar, Avinash; Saada, Julien; Perrault, Isabelle; Amiel, Jeanne; Litzler, Julie; Filhol, Emilie; Elkhartoufi, Nadia; et al.
<x xml:space="preserve">Abstract</x> In a consanguineous family with Joubert syndrome, we identified a homozygous splice site mutation in PDE6D, encoding a prenyl‐binding protein. Proteomic analysis identified INPP5E, whose mutations also lead to JS or MORM syndromes, as novel prenyl‐dependent cargo of PDE6D. Mutant PDE6D shows reduced binding to INPP5E, which fails to localize to primary cilia indicating the requirement of functional PDE6D for correct targeting of INPP5E to the primary cilia. This study provides the first evidence of prenylbinding‐dependent trafficking in ciliopathies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>